A Nearshore Heaving-Buoy Sea Wave Energy Converter for Power Production. (2016) - Youssef, Joseph; Matar, Jean; Rahme, Pierre; Bou-Mosleh, Charbel
Abstract: There exists nowadays an ever-increasing demand for clean and renewable energy, due to the high level of pollution conventional energy production plants produce. Extracting energy from sea waves in Lebanon is a technology that has not yet been developed. In this paper, the potential of harvesting wave energy to produce electrical power on the Lebanese shore is investigated. As such, a compact wave-harvesting device was built. It consists of a float-rack-pinion system that transmits the vertical heaving motion of the waves and converts it into a rotating motion. This in turn is used to produce electricity through an alternator. A prototype was built and successfully tested in shallow water near shore to light up a 3-W lamp. The mechanical design of the manufactured device along with the operation process will be presented in details. In addition, the test results will be summarized along with the potential improvements that can be applied to the system.